The Role of Urodynamic Study in Male with Lower Urinary Track Symptoms and Benign Prostatic Hyperplasia - Abdulqader, Dr. Ahmed Samir; Abdul-Hamid, Dr.Lawand Sardar; Toma, Dr. Tarq Aziz (Academic Journal of Clinicians, 2024)
Background: Urodynamic studies done to assess the function of the bladder and bladder outlet obstruction. Often useful in the assessment and diagnosis of patients presenting with lower urinary tract symptoms (LUTS). Objective: To evaluate the role of urodynamic study in male patients with lower urinary tract symptoms with or without benign prostatic hyperplasia. Patients and Method: This study was conducted as a comparative study for patients taken between 2017 -2019, at Rizgary Teaching Hospital in Erbil city /Kurdistan region/ Iraq. Total of fifty 50 male patients (40-85 years) who underwent urodynamic study for lower urinary tract symptoms and benign prostatic hyperplasia (voiding dysfunction). All patients completed the symptom questionnaire (urgency, frequency, nocturia, difficulty in urination and postvoiding drippling) and the quality of life questionnaire. Results: The mean age of the studied group was 64.7 ± 8.9 (range: 42-85) years. Out of 50 participants, 23 patients had symptoms less than one (1) year duration, 27 patients had symptoms more than one year duration. Conclusion: Patients with irritative symptoms of the benign prostatic hyperplasia after the urodynamic evaluation then management showed a better response to the treatment. Patients with lower urinary tract symptoms without significant prostatic enlargement who had urodynamic study showed better response to management with better quality of life after treatment. Patients with long duration symptoms found to have a larger bladder capacity than those with less than 1 year duration. And uroflowmetery has an additive value to those patients beside urodynamic study.